DETERMINAN KUALITAS LAPORAN KEUANGAN PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2017 - 2021 - Putri, Nazila; Hariani, Swarmilah (Journal Accounting International Mount Hope, 2024)
This research aimed to analyze the influence firm size and leverage on financial reporting quality with profitability as a moderating variabel. The population that the subject of research were companies listed on Bursa Efect Indonesia in the period 2017-2021. The method of determining the sample in this study used purposive sampling technique and obtained 90 sample observation data. This research is casual research and data analysis was done by moderation regression analysis using SPSS version 25 program.The Result of dana analysis showed that firm size had positive effect to financial reporting quality, leverage had no effect to financial reporting quality, profitability couldn’t moderate influence of firm size and leverage towards financial reporting quality.